Respon Pengunjung Terhadap Daya Tarik Tugu Titik Nol Islam Barus Visitor’s Response to the Attractiveness of Tugu Titik Nol Islam Barus - Wahyudi Ramadhan Samosir; Irwan Syari Tanjung (Universitas Muhammadiyah Sumatera Utara, 2022)
One of the recently popular place in Central Tapanuli Regency is the Tugu Titik Nol Islam Barus which is one of the most popular buildings in Central Tapanuli because of the history behind the establishment of the monument, namely as a symbol of the starting point to spread islam in Indonesia. Since it was legalized in 2017, many visitors have come, both local and non local. However, after several years of existence, the construction in Tugu Titik Nol Islam is still relatively ordinary. There is no development, progress, and even tends to decline. The purpose of this study was to determine the visitor's response to the attractiveness of Tugu Titik Nol Islam Barus. The method used in this research is qualitative, by doing in-depth interviews with visitors. From the research results, It’s known that the visitor's response to the attractiveness of Tugu titik Nol Islam Barus is good and positive. Visitors feel that Tugu titik Nol islam is a new icon for Central Tapanuli regency. In addition, the beaches around the monument add to the special attraction of the Tugu Titik Nol islam Barus, because the visitor not only can see the monument directly, but also can enjoy the view of the beach. For development, visitors feel that it is quite good, but still needs maintenance. And for other infrastructure facilities, the visitors considered that they still needed to be improved and equipped again, and also the problem of cleanliness around the monument which also still needed attention.